2018
DOI: 10.1038/s41598-018-33398-8
|View full text |Cite
|
Sign up to set email alerts
|

TRSP is dispensable for the Plasmodium pre-erythrocytic phase

Abstract: Plasmodium sporozoites deposited in the skin following a mosquito bite must migrate and invade blood vessels to complete their development in the liver. Once in the bloodstream, sporozoites arrest in the liver sinusoids, but the molecular determinants that mediate this specific homing are not yet genetically defined. Here we investigate the involvement of the thrombospondin-related sporozoite protein (TRSP) in this process using knockout Plasmodium berghei parasites and in vivo bioluminescence imaging in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Finally, the wells were washed and the slides mounted with antifade solution. Image acquisition and analysis was performed as previously described (26). Briefly, 25 images per (which was not certified by peer review) is the author/funder.…”
Section: In Vitro Invasion and Development Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the wells were washed and the slides mounted with antifade solution. Image acquisition and analysis was performed as previously described (26). Briefly, 25 images per (which was not certified by peer review) is the author/funder.…”
Section: In Vitro Invasion and Development Assaysmentioning
confidence: 99%
“…Finally, the wells were washed and the slides mounted with antifade solution. Image acquisition and analysis was performed as previously described (26). Briefly, 25 images per well, corresponding to a total area of 0.57 mm 2 , were taken using IN Cell Analyzer 2000 (GE Healthcare).…”
Section: In Vitro Invasion and Development Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…TRSP (thrombospondin-related sporozoite protein) is a sporozoite-specific protein containing a TSR domain localized to the rhoptries in oocyst and salivary gland-derived sporozoites [75]. Although a recent study deemed TRSP dispensable in Pb pre-erythrocytic stages [76], earlier work using a different Pb strain suggested that it is involved in hepatocyte invasion, particularly at the entry point, since a marked reduction of knockout intracellular sporozoites and a rise in the frequency of partially invaded parasites was observed, suggesting a role in completing cell entry [77]. The roles of RON2 and RON11 in substrate attachment and motility consequently impact the invasion of hepatocytes [22,26].…”
Section: Box 2 Biogenesis and Exocytosis Of Micronemes And Rhoptries In Sporozoitesmentioning
confidence: 99%
“…Parasites were prepared as previously described: Neospora caninum tachyzoites (Nc-1, ATCC 50843) (36), Plasmodium berghei ANKA strain blood merozoites (clone 676cl1) (37), Trypanosoma brucei brucei Lister 427 bloodstream forms (38), Leishmania major strain LV39, and Leishmania tarentolae strain Parrot-TarII promastigotes (39). A green fluorescent protein (GFP)-expressing T. brucei brucei Lister 427 line was engineered by cloning an enhanced gfp into a modified pHD1034 vector where the puromycin resistance cassette was replaced by the hygromycin resistance from the pHD1145 vector.…”
Section: Immunostainingmentioning
confidence: 99%